Rasio Keuangan Koperasi (Studi pada Koperasi Pegawai Republik Indonesia “Angkasa” Rri Yogyakarta) - Veronica Suwarmi (EXERO : Journal of Research in Business and Economics, 2019)
This study aims to determine the financial condition and development of KPRI "Angkasa" RRI Yogyakarta in 2012-2016 using the ratio of liquidity, solvency, profitability and activity. The type of research is a case study at KPRI "Angkasa" RRI Yogyakarta. Data collection techniques are documentation and interviews. The data analysis technique is calculating the ratios of liquidity, solvency, profitability and activity, analyzing using trend and common size. The results of the analysis show that the level of liquidity as measured by the current ratio in 2012-2016 is categorized as very good. The level of solvency as measured by the total debt to equity ratio and the total debt to total assets ratio in 2012-2016 is good, except for 2014 which is quite good. The level of profitability measured by net profit margin in 2012-2016 is categorized as very good, except for 2013 it is categorized as good, for return on assets in 2012-2016 it is categorized as quite good, the profitability of own capital in 2012-2016 is categorized as poor. The level of activity as measured by asset turnover in 2012-2016 is categorized as not good. The results of the analysis of the trend current ratio, total debt to equity ratio, total debt to total asset ratio and net profit margin in 2012-2016 have increased performance, while return on assets, own capital earnings and asset turnover have decreased performance. The results of the common size analysis on the balance sheet and the remaining earnings tend to decrease.